Enhancing independence of local auditing services by profiting from experiences of the Big4 group (KPMG, Deloitte, PWC E&Y) operating in Vietnam market - Nguyen Hoang Tien; Tran Minh Thuong; Le Doan Minh Duc; Nguyen Thi Hoang Yen (Cogent Business & Management, 2019)
In Vietnam, auditor independence is guided by the Code of Professional Ethics for Accounting and Auditing issued in accordance with Circular No. 70/2015/TT-BTC of the Ministry of Finance. Independence is the first and most important principle for the professional ethics of auditors. Independence is also an essential component of quality assurance of the auditing service. At present, there are many studies on auditor independence in general and on the relationship between non-audit services and auditor independence over different time and space. The auditing industry in Vietnam is still in a burgeoning state, and its economic and sociocultural context as well as the institutional settings are very specific compared to those of other countries in the world. The article investigates the issue of how local auditing companies could improve their independence and as a result their quality of auditing services based on experiences of the Big4 group already present and operating in Vietnam market.
Keywords: 650; auditor independence; KPMG; Deloitte; PwC; E&Y; Vietnam